Characterization charcoal and activated carbon from starry triggerfish (Abalistes stellaris) bone activated using zinc chloride to reduce Cr6+ - Lia Handayani; Nurhayati Nurhayati; Faisal Syahputra; Azwar thaib; Yayuk Astuti; Adi Darmawan; Ainal Mardhiah (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Starry triggerfish bone is the leftovers of fish products, and the utilization as carbon active is still minimal. Fish bones are organic waste containing carbon; therefore, they could be utilized as adsorbents (charcoal and activated carbon). This study aims to determine the characteristics of charcoal and activated carbon produced from starry triggerfish bone. The study about making charcoal and carbon active from starry triggerfish bone waste has been conducted using combined physics and chemical activation. physics activation is conducted at temperatures of 500°C, 600°C, 700°C, 800°C (CFB-500; CFB-600, CFB-700 and CFB-800), then the chemical activation using ZnCl2 15% (AC-500, AC-600, AC-700 and AC-800). Finding charcoal and carbon active characteristics such as surface area, analysis composition chemistry and morphology using BET-Ads, X-ray diffraction (XRF), and scanning electron microscopy (SEM). Based on chemical composition, CFB-600 has a better proportion of impurities than other CFBs and ACs. The activated CFB-500 with an activator (AC-500) experienced a significant increase of surface. It was better compared to others that reached 73.07 m2/g, while in the other treatments, the increase of surface area from CFB to AC ≤40 m2/g. Thus, it can be concluded the increase in temperature is not directly proportional to the increase in surface area. The temperature of 500oC is the optimal temperature obtained in this study and has a significant increase in surface area and absorption efficiency of Cr6+ of 87.47%.